2013
DOI: 10.1002/mrm.25035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diffusion time on liver DWI: An experimental study of normal and fibrotic livers

Abstract: Our results demonstrated the Δ dependent diffusion measurements, indicating restricted diffusion in both normal and fibrotic liver. D(true) measured with long Δ acted as a more sensitive index of the pathological alterations in liver microstructure during fibrogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 61 publications
8
28
1
Order By: Relevance
“…Our results for ADC measurements of water and urea in solution agree with those of prior studies, as do the results for the water ADC of normal mouse liver . Using a spectroscopic DW sequence, Sogaard et al observed a similar compartmentalization effect in muscle with HP [1‐ 13 C]pyruvate as the extracellular agent, and HP [1‐ 13 C]lactate as the intracellular compound.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our results for ADC measurements of water and urea in solution agree with those of prior studies, as do the results for the water ADC of normal mouse liver . Using a spectroscopic DW sequence, Sogaard et al observed a similar compartmentalization effect in muscle with HP [1‐ 13 C]pyruvate as the extracellular agent, and HP [1‐ 13 C]lactate as the intracellular compound.…”
Section: Discussionsupporting
confidence: 90%
“…One possible reason that we did not detect a change with progression of fibrosis is that there was not severe enough liver fibrosis in this mouse model to detect a significant change (maximum fibrosis grade was 3 on a scale from 0 to 6). This possibility is supported by the fact that we did not observe a decrease even in the proton ADC, which has been observed by other researchers using similar but more severe animal models of liver fibrosis and in humans with advanced fibrosis . In a study performed in a CCl 4 rat model of liver fibrosis, 1 H ADC decreased from ∼(1.5 ± 0.3) × 10 −3 mm 2 /s in healthy livers to ∼(1.0 ± 0.2) × 10 −3 mm 2 /s in fibrotic livers with 14% fibrosis volume density .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This effect was used to estimate myofibre size and sarcolemmal permeability. Since then, other studies have measured the time dependence of diffusivity in skeletal muscle, other organs and other pathologies . More recently, structural parameters, such as fibre size and membrane permeability of human calf muscles, have been quantified in both adult healthy subjects and patients using a biophysical model applied to time‐dependent diffusion measurements.…”
Section: Introductionmentioning
confidence: 99%